Evidence for Shared Genetic Aetiology Between Schizophrenia, Cardiometabolic, and Inflammation-Related Traits: Genetic Correlation and Colocalization Analyses. Issue 1 (11th January 2022) - Perry, Benjamin I; Bowker, Nicholas; Burgess, Stephen; Wareham, Nicholas J; Upthegrove, Rachel; Jones, Peter B; Langenberg, Claudia; Khandaker, Golam M
Abstract: Background: Schizophrenia commonly co-occurs with cardiometabolic and inflammation-related traits. It is unclear to what extent the comorbidity could be explained by shared genetic aetiology. Methods: We used GWAS data to estimate shared genetic aetiology between schizophrenia, cardiometabolic, and inflammation-related traits: fasting insulin (FI), fasting glucose, glycated haemoglobin, glucose tolerance, type 2 diabetes (T2D), lipids, body mass index (BMI), coronary artery disease (CAD), and C-reactive protein (CRP). We examined genome-wide correlation using linkage disequilibrium score regression (LDSC); stratified by minor-allele frequency using genetic covariance analyzer (GNOVA); then refined to locus-level using heritability estimation from summary statistics (ρ-HESS). Regions with local correlation were used in hypothesis prioritization multi-trait colocalization to examine for colocalisation, implying common genetic aetiology. Results: We found evidence for weak genome-wide negative correlation of schizophrenia with T2D (rg = −0.07; 95% C.I., −0.03, 0.12; P = .002) and BMI (rg = −0.09; 95% C.I., −0.06, −0.12; P = 1.83 × 10 −5 ). We found a trend of evidence for positive genetic correlation between schizophrenia and cardiometabolic traits confined to lower-frequency variants. This was underpinned by 85 regions of locus-level correlation with evidence of opposing mechanisms. Ten loci showed strong evidence of colocalization. Four of those (rs6265 ( BDNF ); rs8192675 ( SLC2A2 ); rs3800229 ( FOXO3 ); rs17514846 ( FURIN )) are implicated in brain-derived neurotrophic factor (BDNF)-related pathways. Conclusions: LDSC may lead to downwardly-biased genetic correlation estimates between schizophrenia, cardiometabolic, and inflammation-related traits. Common genetic aetiology for these traits could be confined to lower-frequency common variants and involve opposing mechanisms. Genes related to BDNF and glucose transport amongst others may partly explain the comorbidity between schizophrenia and cardiometabolic disorders.